Importance of team height to winning games in the National Basketball Association - Teramoto, M.; Cross, C. L. (International Journal of Sports Science & Coaching, 2018)
A recent trend in the National Basketball Association, so-called "small-ball," questions the importance of height in basketball. The present study examined the association of team height, defined as an average height of players weighted by playing time, to team performance in the 2006-2007 through 2015-2016 National Basketball Association seasons. Relationships of team height to winning games, to offensive and defensive ratings, and to four factors were assessed using Pearson`s correlation coefficients. A generalized estimating equation was used to examine the association of team height to winning games, separately for the Eastern and Western Conferences, while using performance variables above as covariates. Team height had significant positive correlations with offensive and defensive rebounds, and had a significant inverse relationship with the opponent`s turnovers (p<0.05). After adjusting for the team performance variables, team height was found to be an insignificant predictor of winning games in the regular seasons (p>0.05). In the playoffs, the interaction between team height and offensive rating was significant (p<0.05). A follow-up analysis revealed that teams in the Eastern Conference had higher winning percentages with smaller lineups, whereas those in the Western Conference performed better with bigger lineups. A significant interaction was also found between team height and effective field goal percentage or free throw rate in the Eastern Conference playoffs (p<0.05). Specifically, bigger lineups were associated with higher winning percentages for teams with lower effective field goal percentages and higher free throw rates. These results may suggest that team height is important in winning games in the playoffs.